2015
DOI: 10.1261/rna.046482.114
|View full text |Cite
|
Sign up to set email alerts
|

The small RNA content of human sperm reveals pseudogene-derived piRNAs complementary to protein-coding genes

Abstract: At the end of mammalian sperm development, sperm cells expel most of their cytoplasm and dispose of the majority of their RNA. Yet, hundreds of RNA molecules remain in mature sperm. The biological significance of the vast majority of these molecules is unclear. To better understand the processes that generate sperm small RNAs and what roles they may have, we sequenced and characterized the small RNA content of sperm samples from two human fertile individuals. We detected 182 microRNAs, some of which are highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 66 publications
6
61
0
1
Order By: Relevance
“…The overall length distribution of small RNAs revealed that the dominant reads from pig seminal plasma, epididymal sperm and ejaculated sperm are 18-26 nucleotides (Fig. 1A), which is distinct from that observed in adult testes (Kowalczykiewicz et al 2014, Gebert et al 2015, where two peaks (18-25 nucleotides and 26-32 nucleotides) are observed, and in human sperm (24-31 nucleotides) (Pantano et al 2015). The majority of the 26-32 nucleotide small RNAs in the pig testes and the human sperm are piRNAs (Kowalczykiewicz et al 2014, Gebert et al 2015, Pantano et al 2015, which are actively involved in the retrotransposon silencing that protects the integrity of the genome.…”
Section: Diverse Small Rna Classes Were Enriched In Ejaculated Spermmentioning
confidence: 80%
See 4 more Smart Citations
“…The overall length distribution of small RNAs revealed that the dominant reads from pig seminal plasma, epididymal sperm and ejaculated sperm are 18-26 nucleotides (Fig. 1A), which is distinct from that observed in adult testes (Kowalczykiewicz et al 2014, Gebert et al 2015, where two peaks (18-25 nucleotides and 26-32 nucleotides) are observed, and in human sperm (24-31 nucleotides) (Pantano et al 2015). The majority of the 26-32 nucleotide small RNAs in the pig testes and the human sperm are piRNAs (Kowalczykiewicz et al 2014, Gebert et al 2015, Pantano et al 2015, which are actively involved in the retrotransposon silencing that protects the integrity of the genome.…”
Section: Diverse Small Rna Classes Were Enriched In Ejaculated Spermmentioning
confidence: 80%
“…Conversely, the current study revealed that the diversity of small RNAs across the three libraries is generally similar. In addition to mRNAs, the diversity of the population of the sperm RNAs has now been extended to several non-coding RNAs, including miRNAs, piRNAs (Amanai et al 2006, Krawetz et al 2011, Pantano et al 2015, endo-siRNAs , small RNAs derived from tRNA, rRNA, snRNA and snoRNA (Peng et al 2012) and lncRNA . The sperm miRNA has been reported most extensively and identified in all mammal species examined, including humans, mice, rats, rabbits, bulls, pigs and stallions (Amanai et al 2006, Cornwall 2009, Krawetz et al 2011, Das et al 2013, Stowe et al 2014, Kasimanickam & Kastelic 2016.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations